E EFEKTIFITAS EDUKASI DENGAN MEDIA BERBASIS AUDIO VISUAL TERHADAP PENGETAHUAN KELUARGA TENTANG ROM PADA PASIEN STROKE: LITERATURE REVIEW - Siti Nabella Elma Qaryati (Journal of Nursing Invention, 2021)
ABSTRACT Background: Problems that commonly occur in post-stroke patients are partial paralysis of the body, stiffness or weakness in the muscles. Lack of family knowledge regarding how to mobilize patients will be an obstacle in the treatment process. Family has an important role in patient care, so it is important to increase family knowledge by providing education. Namely Education With Audio Visual Based Media Against Family Knowledge About Rom (Range Of Motion) Objective: Knowing the Effectiveness of Education with Audiovisual Based Media Against Family Knowledge About ROM (Range of Motion) in Stroke Patients. Method : This research uses the Literature Review Method. Literature sourcesused in this study were trace trough Google Scholar, Portal Garuda, and Biomed Central. Results: From 10 literatures, it is found that the length of time from the audiovisual media can be given to families to assess how effective the education is given, there is also the virtue of audiovisual media which is considered good and effective enough to be used as an educational medium to increase family knowledge. Conclusion: The use of audiovisual media as one of the new innovations in the implementation of education that can be used by health workers is considered very effective to increase knowledge, especially family knowledge about health, one of which is family knowledge about how to do ROM exercises.